Assessing cell polarity reversal degradation phenomena in PEM fuel cells by electrochemical impedance sectroscopy - Travassos, Maria Antónia (2013)
Electrochemical impedance spectroscopy (EIS) is identified as one of the most promising in-situ diagnostics tools available for assessing fuel cell ageing and degradation. In this work, the degradation phenomena caused by cell polarity reversal due to fuel starvation of an open cathode 16 membrane electrode assembly (MEA) – low power (PEM) fuel cell (15 W nominal power) – is reported using EIS as a base technique. Measuring the potential of individual cells, while the fuel cell is on load, was found instrumental in assessing the “state of health” of cells at fixed current. Location of affected cells, those farthest away from hydrogen entry in the stack, was revealed by very low or even negative potential values. EIS spectra were taken at selected break-in periods during fuel cell functioning. The analysis of impedance data was made using an a priori equivalent circuit describing the transfer function of the system in question –equivalent circuit elements were evaluated by a complex non-linear least square (CNLS) fitting algorithm, and by calculating and analyzing the corresponding distribution of relaxation times (DRT). Results and interpretation of cell polarity reversal due to hydrogen starvation were complemented with ex-situ MEA cross section analysis, using scanning electron microscopy. Electrode thickness reduction and delamination of catalyst layers were observed as a result of reactions taking place during hydrogen starvation. Carbon corrosion and membrane degradation by fluoride depletion are discussed.